Ultrathin Strut Biodegradable Polymer Sirolimus‐Eluting Stent Versus Durable‐Polymer Everolimus‐Eluting Stent for Percutaneous Coronary Revascularization: 2‐Year Results of the BIOSCIENCE Trial. Issue 3 (15th March 2016) - Zbinden, Rainer; Piccolo, Raffaele; Heg, Dik; Roffi, Marco; Kurz, David J.; Muller, Olivier; Vuilliomenet, André; Cook, Stéphane; Weilenmann, Daniel; Kaiser, Christoph; Jamshidi, Peiman; Franzone, Anna; et al.
Abstract : Background: No data are available on the long‐term performance of ultrathin strut biodegradable polymer sirolimus‐eluting stents (BP‐SES). We reported 2‐year clinical outcomes of the BIOSCIENCE (Ultrathin Strut Biodegradable Polymer Sirolimus‐Eluting Stent Versus Durable Polymer Everolimus‐Eluting Stent for Percutaneous Coronary Revascularisation) trial, which compared BP‐SES with durable‐polymer everolimus‐eluting stents (DP‐EES) in patients undergoing percutaneous coronary intervention. Methods and Results: A total of 2119 patients with minimal exclusion criteria were assigned to treatment with BP‐SES (n=1063) or DP‐EES (n=1056). Follow‐up at 2 years was available for 2048 patients (97%). The primary end point was target‐lesion failure, a composite of cardiac death, target‐vessel myocardial infarction, or clinically indicated target‐lesion revascularization. At 2 years, target‐lesion failure occurred in 107 patients (10.5%) in the BP‐SES arm and 107 patients (10.4%) in the DP‐EES arm (risk ratio [RR] 1.00, 95% CI 0.77–1.31, P =0.979). There were no significant differences between BP‐SES and DP‐EES with respect to cardiac death (RR 1.01, 95% CI 0.62–1.63, P =0.984), target‐vessel myocardial infarction (RR 0.91, 95% CI 0.60–1.39, P =0.669), target‐lesion revascularization (RR 1.17, 95% CI 0.81–1.71, P =0.403), and definite stent thrombosis (RR 1.38, 95% CI 0.56–3.44, P =0.485). There were 2 cases (0.2%) of definite very late stent thrombosis in the BP‐SES arm and 4 cases (0.4%) in the DP‐EES arm ( P =0.423). In the prespecified subgroup of patients with ST‐segment elevation myocardial infarction, BP‐SES was associated with a lower risk of target‐lesion failure compared with DP‐EES (RR 0.48, 95% CI 0.23–0.99, P =0.043, P interaction =0.026). Conclusions: Comparable safety and efficacy profiles of BP‐SES and DP‐EES were maintained throughout 2 years of follow‐up. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01443104.